2017
DOI: 10.1039/c7sm00739f
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical behavior of microgels of interpenetrated polymer networks

Abstract: Microgel suspensions of an interpenetrated Polymer Network (IPN) of PNIPAM and PAAc in DO have been investigated through dynamic light scattering as a function of temperature, pH and concentration across the Volume Phase Transition (VPT). The dynamics of the system is slowed down under H/D isotopic substitution due to different balance states between polymer/polymer and polymer/solvent interactions suggesting the crucial role played by H-bonding. The swelling behavior, reduced with respect to PNIPAM and water,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 80 publications
9
57
1
Order By: Relevance
“…59 This particular kind of microgels has recently gathered a lot of interest because of their intriguing fragility behavior: as the amount of charges increase, these systems exhibit features of strong glass-formers, a rather unique example in soft matter. 16,17 A recent work 60 has put forward the idea that this behavior directly stems from charge effects, which also increase the softness of the particles, as confirmed in the present work. It would thus be very interesting to address the behavior of IPN microgels in future works.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…59 This particular kind of microgels has recently gathered a lot of interest because of their intriguing fragility behavior: as the amount of charges increase, these systems exhibit features of strong glass-formers, a rather unique example in soft matter. 16,17 A recent work 60 has put forward the idea that this behavior directly stems from charge effects, which also increase the softness of the particles, as confirmed in the present work. It would thus be very interesting to address the behavior of IPN microgels in future works.…”
Section: Discussionsupporting
confidence: 79%
“…Since such a ratio has been previously adopted as a measure of the particle softness, 16,17 this suggests that more charged microgels are softer than less charged or neutral ones, in agreement with experimental findings.…”
Section: Temperature-driven Swelling Of Charged Microgels With Explicsupporting
confidence: 82%
“…Moreover, they are used as model systems in soft matter chemistry and physics, thanks to their phase behavior (volume phase transition) and colloidal properties . The volume phase transition of the temperature‐ and pH‐sensitive IPN microgel made of interpenetrating PNIPAM and polyacrylic acid (PAAc) has been investigated in the last years, as well as the dynamical properties in the concentration region around and above the overlap value, across the volume phase transition temperature at different pH values …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] The volume phase transition of the temperature-and pH-sensitive IPN microgel made of interpenetrating PNIPAM and polyacrylic acid (PAAc) has been investigated in the last years, [16][17][18] as well as the dynamical properties in the concentration region around and above the overlap value, across the volume phase transition temperature at different pH values. [19][20][21] Another important issue concerns the role of the electrostatic interactions in determining the stability conditions of the microgel and it is commonly faced by considering the effective interaction potential between two sphere-like particles. [11,12,14,[22][23][24][25][26] For charged particles the potential takes into account the effect of neutralization of the bare charge by counterions.…”
Section: Introductionmentioning
confidence: 99%
“…Significant changes in m k for soft colloids have been reported previously [35,[40][41][42], but the physics underlying this behavior in terms of the interparticle interaction has remained unclear, and perhaps even controversial. It was found that there is a crossover from fragile to strong glasses in deformable microgels when the internal elasticity of the particles decreases.…”
Section: Stiffness Of the Dlvo Potential And Dramatic Fragility Changesmentioning
confidence: 99%